The Zombic Hunch: Extinction of an Intuition? - Dennett, Daniel C. (Tufts Archival Research Center, 2005)
Dennett, Daniel C. "The Zombic Hunch: Extinction of an Intuition?" In Philosophy at the New Millenium, edited by Anthony O'Hear, 27-43. Cambridge: Cambridge University Press, 2001.